Tensión entre el Tribunal Constitucional polaco y el Tribunal de Justicia de la Unión Europea: A propósito de la independencia judicial - Soto Prats, Bárbara (2026)
A process is fair if an independent and impartial court judges the case before it, although in practice this is not always the case. This essay analyzes the case of Poland and explains how its history has affected the principle of judicial independence. The position of the Polish Constitutional Court against the different resolutions issued by the Court of Justice of the European Union is exposed and criticized, which has caused an increase in tension between these courts and the questioning of whether Poland will continue to be a member of the European Union.